Balance Sheet Management: The Case of Short‐Term Obligations Reclassified as Long‐Term Debt - Gramlich, Jeffrey D.; McAnally, Mary Lea; Thomas, Jacob (Journal of Accounting Research, 2001)
We investigate potential management of balance sheet ratios by a sample of firms that reclassify short‐term obligations to long‐term debt and subsequently declassify that debt (return it to the current liability section). Although aggregate measures of liabilities and equity remain unchanged when firms reclassify (declassify), the practice does increase (decrease) reported measures of liquidity, such as the current ratio, and long‐term leverage. Our results suggest that firms reclassify and declassify to smooth reported liquidity and leverage, relative to the prior year and to industry benchmarks. Our evidence is also consistent with firms working around restrictive debt covenants.